2011
DOI: 10.1016/j.ydbio.2011.04.028
|View full text |Cite
|
Sign up to set email alerts
|

The nucleolar GTP-binding proteins Gnl2 and nucleostemin are required for retinal neurogenesis in developing zebrafish

Abstract: Nucleostemin (NS), a member of a family of nucleolar GTP-binding proteins, is highly expressed in proliferating cells such as stem and cancer cells and is involved in the control of cell cycle progression. Both depletion and overexpression of NS result in stabilization of the tumor suppressor p53 protein in vitro. Although it has been previously suggested that NS has p53-independent functions, these to date remain unknown. Here, we report two zebrafish mutants recovered from forward and reverse genetic screens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…There are some studies that addressed this question by investigating the effect of nucleostemin depletion in cells with wild-type and mutant p53, but they reached opposite conclusions. In support of the p53-dependency of nucleostemin activity, it has been shown that cell cycle arrest or apoptosis that is triggered by knockdown or knockout of nucleostemin can be completely or partially reversed by p53 knockdown (Ma and Pederson, 2007;Paridaen et al, 2011;Yamashita et al, 2013). Furthermore, nucleostemin has been found to directly interact with MDM2 to modulate the activity of p53 (Dai et al, 2008;Meng et al, 2008).…”
Section: Anole (46%)mentioning
confidence: 93%
“…There are some studies that addressed this question by investigating the effect of nucleostemin depletion in cells with wild-type and mutant p53, but they reached opposite conclusions. In support of the p53-dependency of nucleostemin activity, it has been shown that cell cycle arrest or apoptosis that is triggered by knockdown or knockout of nucleostemin can be completely or partially reversed by p53 knockdown (Ma and Pederson, 2007;Paridaen et al, 2011;Yamashita et al, 2013). Furthermore, nucleostemin has been found to directly interact with MDM2 to modulate the activity of p53 (Dai et al, 2008;Meng et al, 2008).…”
Section: Anole (46%)mentioning
confidence: 93%
“…We have studied its expression in order to characterize in more detail the epigenetic state of the RPE. Nucleostemin (a marker of low-differentiated cells) has been identified in pluripotent embryonic stem cells and low-differentiated neural cells in both vertebrates and invertebrates [112,113,114,115]. It has various functions and is involved in the regulation of RNA polymerase I activity, transcription, chromatin structure, etc.…”
Section: Epigenetic Factors In Cell Of Normal Rpe and At Early Stamentioning
confidence: 99%
“…During neural lineage commitment there is no direct evidence that rRNA transcription is inhibited; it is likely, however, that mechanisms involving nucleolar dynamics could be in play. For example in brain and retina the levels of the nucleolar protein nucleostemin, a controller of pre-rRNA processing, are rapidly reduced before cell cycle exit and neural differentiation [4, 5], suggesting that rRNA biosynthesis may have a regulatory effect on neurogenesis.…”
Section: Non-traditional Roles Of the Nucleolus Under Physiological Cmentioning
confidence: 99%